A-Sian-Ra Wat: Social Roles’ Study; a Case Study of the Book “89 Years of King Bhumibol” - La-or, Sajjabhoum (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Eulogy (A-Sian-Ra Wat) is the literature praised honor of kings, royal family and aristocrats. Thailand was influenced by India. It has been consistently appeared from the Sukhothai period to present time. What is the role of A-Sian Wat? A case study from a book, ‘89 Years of King Bhumibol’, and from all 89 verses was found seven roles; 1) The role to raise awareness in the royal grace as the king is the spiritual anchor of Thai people, 2) The role to raise awareness in royal duties, 3) The role to raise awareness in admiring him as the divine king, 4) The role to raise awareness in the philosophy and king’s speech, 5) The role to instill conscience to Thai people in doing good deeds for the king, 6) The role to instill conscience to Thai people in repaying kindness of the king, 7) The role to instill conscience to Thai people in preserving the heritage of Thailand.